Reviving the Broad Guidelines of State Policy (GBHN) as the Product of People’s Consultative Assembly (MPR) in the Presidential Government System in Indonesia - Yusdiyanto Yusdiyanto (Fiat Justisia: Jurnal Ilmu Hukum, 2018)
The research aims to enlight the overview about the urgent of the Broad Guidelines of State Policy (GBHN) as the product of the People’s Consultative Assembly (MPR) by using the dogmatic approach. The amendment of the 1945 Constitution has changed the Indonesian constitutional system. According to the article 2 paragraph (1) of the 1945 Constitution, highest authority remains in the hands of the people and is carried out according to the Constitution. The constitutional design of the Indonesian government system is presidential. However, the implementation often reaps many obstacles and problems, the consequences of amendments, eliminating the authority of the People’s Consultative Assembly (MPR) in terms of electing the President and Vice President, and determining the Broad Guidelines of State Policy (GBHN). MPR is no longer placed as the highest institution of the country and the perpetrators of popular sovereignity. The Constitution which is the holder of popular sovereignty in the practice adheres to a clear and strict understanding of the separation of powers. Like in the legislative field there are People’s Consultative Assembly (MPR), House of Representatives (DPR) and Regional Representative Board (DPD); in the executive field there are Presidents and Vice Presidents elected by the people; in the judicial sector there are the Supreme Court, the Constitutional Court and the Judicial Commission; in the field of financial supervision there is a Indonesian Supreme Audit Institution (BPK). Changes in the position, function and authority of the MPR have implications for the emergence of the National Development Planning System and the National Long-Term Development Plan which became the authority of the elected President. The President that won the election as a basic guidelines for implementing development as the replacement of the GBHN.